Adenoma of the Nonpigmented Ciliary Epithelium in the Phthisic Eye. (June 2013) - Takahashi, Yasuhiro; Takahashi, Emiko; Goto, Hiroshi; Kakizaki, Hirohiko
Abstract Purpose: To report a case of adenoma of the nonpigmented ciliary epithelium (NPCE) in a phthisic eye. Methods: The clinical and histopathological findings of the case were reported. Results: A 79-year-old man with a left phthisic eye had suffered from severe left ocular pain for 2 months. At the first examination, the intraocular pressure was 48 mm Hg OS. Slit lamp examination of the left eye revealed an opaque cornea with a band-shaped keratopathy and a hematoma in the anterior chamber, precluding further intraocular examination. Computed tomography revealed a left intraocular heterogeneous lesion with posterior expansion, which was consistent with a hematoma. Evidence of an intraocular tumor before the evisceration was not found. However, histopathological examination of the eviscerated specimen disclosed a tumor comprising tubular components with papillary epithelial proliferation, which was classified as adenoma of the NPCE. Conclusions: The current case suggests a necessity for histopathological examination after evisceration to detect components related to a phthisis bulbi, including adenoma of the NPCE.